2017
DOI: 10.15174/au.2017.1203
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of pesticides residues in northwestern Mexico rivers

Abstract: In Mexico, use of river water for households, agriculture and industry has adversely affected aquatic environment through chemical and microbial contamination. The aim of this study was to determine pesticide residues levels in water of rivers from central Sinaloa State, Northwestern Mexico. In samples obtained from July 2008 to June 2009 pesticides residues detected were lindane, heptachlor, endosulfan, dicloro difenil tricloroetano (DDT), diazinon, chlorpyrifos, permethrin, methyl parathion, cyromazine, ethi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 0 publications
0
9
0
2
Order By: Relevance
“…However, in order to understand the resultant risks to environment and population health requires improvement in existing knowledge with regards to the fate of herbicides residues in ambient water bodies. The ability of these compounds to accumulate in the environment and their toxicity to aquatic lives, humans, and wildlife is a concern (Amweg et al, 2006;Parsons et al, 2009;Buah-Kwofie and Humphries, 2017;Gama et al, 2017;Morales et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, in order to understand the resultant risks to environment and population health requires improvement in existing knowledge with regards to the fate of herbicides residues in ambient water bodies. The ability of these compounds to accumulate in the environment and their toxicity to aquatic lives, humans, and wildlife is a concern (Amweg et al, 2006;Parsons et al, 2009;Buah-Kwofie and Humphries, 2017;Gama et al, 2017;Morales et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…With the same focus, Leyva-Morales et al (2017) assessed the quality of river water from central Sinaloa (Humaya, Tamazula and Culiacan rivers) by monitoring residual pesticides. Their results showed that the following chemicals were present: lindane (0.0041-0.0104μg/L), endosulfan (0.0198-0.03601μg/L), heptachlor, dichlorodiphenyltrichloroethane (0.0525μg/L), diazinon (0.0211-0.0403μg/L), chlorpyrifos, methyl parathion, cyromazine (0.1961μg/L), permethrin (0.2351μg/L), ethion, carbofenothion, lambda cyhalotrine, pyrimicarb, aldrin (0.0099-0.1023μg/ L) and malathion.…”
Section: Pharmaceuticals Personal Care Products and Pesticides In The Aquatic Environment In Mexicomentioning
confidence: 99%
“…Their results showed that the following chemicals were present: lindane (0.0041-0.0104μg/L), endosulfan (0.0198-0.03601μg/L), heptachlor, dichlorodiphenyltrichloroethane (0.0525μg/L), diazinon (0.0211-0.0403μg/L), chlorpyrifos, methyl parathion, cyromazine (0.1961μg/L), permethrin (0.2351μg/L), ethion, carbofenothion, lambda cyhalotrine, pyrimicarb, aldrin (0.0099-0.1023μg/ L) and malathion. Leyva-Morales et al (2017) suggested that pesticide contamination derived mainly from runoffs of polluted soil toward rivers.…”
Section: Pharmaceuticals Personal Care Products and Pesticides In The Aquatic Environment In Mexicomentioning
confidence: 99%
“…In Costa Rica, pesticide residues have been detected in various geographical regions of the country, including the Caribbean [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ], the northern zone [ 12 ], the North Pacific [ 13 , 14 , 15 ], the South Pacific [ 16 ], and the horticultural areas of Pacayas and Zarcero in the Central Volcanic Mountain Range [ 17 , 18 ]. In the last 10 years, Cornejo et al [ 19 , 20 ] also detected several pesticide residues in Panama, Barizon et al [ 21 ] in Brazil, Hernández et al [ 22 ] in Colombia, Deknock et al [ 23 ] in Ecuador, Leyva Morales et al [ 24 ] in Mexico, and Cárdenas et al [ 25 ] in Venezuela.…”
Section: Introductionmentioning
confidence: 99%